Improving the Performance of Soil Using Sustainable Geopolymer - Alaa Salim; Alaa H. J. Al-Rkaby (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Soil stabilization is a common technique to improve the mechanical properties of the soil in term of increasing its strength and decreasing the associated settlement. The new sustainable materials have been emerged as alternative to the traditional binders such as the cement and the lime. These materials can be used in the shallow and deep soil mixing. This paper reviewed the mechanism of the soil stabilization, the traditional binder and the sever impacts on the environment, the new echo-friendly materials, deep soil mixing technique, and the geopolemerization. The results showed significant enhancement of the shear strength of the geopolymerized silt where the strength was increased by more than 6 times. This enhancement may be attributed to the developed geopolymer-jel NASH that filled the voids, surrounded and cemented the soil particles. Consequently, this matrix considered as a novel precursor for using in the soil injecting and grouting technique.